Green Digital Marketing: Startegy For Environmentally Conscious SMEs - Dio Samudra; Zahrotul Jannah; Hatma Rahmah; Zahirotul Wirda; Silvi Rohmawati; Ikin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Green digital marketing has emerged as a crucial strategy for environmentally conscious Small and Medium-sized Enterprises (SMEs) in the face of growing consumer awareness and demand for sustainable practices. This approach integrates eco-friendly principles with digital marketing techniques, allowing SMEs to communicate their sustainability efforts while minimizing their environmental impact effectively. By leveraging various digital platforms and tools, such as social media, content marketing, and search engine optimization, SMEs can enhance their brand image, engage eco-conscious consumers, and gain a competitive edge. However, implementing green digital marketing strategies presents unique challenges for SMEs, including limited resources and the need for authentic messaging. This paper explores the critical components of green digital marketing, its benefits for environmentally conscious SMEs, and practical strategies for implementation. It also examines the potential obstacles and proposes solutions to help SMEs successfully navigate the intersection of sustainability and digital marketing in today's competitive business landscape.